EXPLORING ORGANIZATIONAL RELATIONSHIPS IN THE POST-ACUTE CARE MARKET. (11th November 2018) - Tyler, D; Grabowski, D C
Abstract: The post-acute care (PAC) policy environment is rapidly changing. Such changes are affecting how organizations such as hospitals, skilled nursing facilities (SNFs), and managed care organizations (MCOs) within the PAC market interact. As part of a National Institute on Aging funded program project (P01), we conducted a series of case studies in order to explore the changing relationships among these organizations and how these have been affected by provisions of the Affordable Care Act. Between March and November of 2015, we visited eight cities in the US that varied in region of the country, county size, and Medicare managed care penetration and interviewed 154 staff in 16 hospitals, 25 SNFs, and 10 MCOs. In a related study, we returned to five of those cities and interviewed 98 patients recently admitted for PAC to 14 of the SNFs to learn about their experiences. In this symposium we will report a number of the key findings from this research, including 1) how MCOs work with hospitals and SNFs to control SNF selection and length of stay; 2) the unintended consequences of reduced SNF length of stay; 3) the divergent approaches to PAC management being used by two different health care systems in one city; and 4) the experiences of patients who are being discharged from hospitals to SNFs. The findings highlight some of the major changes in PAC and health care today.